A simple discrete-element model for numerical studying the dynamic thermal response of granular materials - Ze-Xiang Wu; Lei Yang; Zhe Wang; Ying-Chun Zhuang; Dong-Mei Tu (Materials Research Express, 2021)
This paper aims to investigate the influence of periodicity temperature change on the properties of dry granular materials in macroscopic and microscopic. A series of cyclic thermal consolidation tests have been carried out based on the discrete element method (DEM) that incorporate particles’ volumetric thermal expansion coefficient. The simulation of the direct shear test was carried out on the samples after thermal cycling. Results showed that thermally-induced volumetric strain accumulation of the specimen can be calculated by the DEM model, based on the two-dimensional particle flow code (PFC2D) software. The lateral pressure degraded concomitantly thanks to decreases in particles’ horizontal contact during periodic thermal cycling. In addition, the shear dilatancy level decreases during the shearing process with the number of thermal cycles. Both the size and anisotropy of the normal contact force and contact number and the force chain are affected by the temperature cycle. Finally, the results of this paper have a certain reference for the engineering practice, such as thermal piles or others, when granular materials are subjected to thermal cycling.